Associations between variants of bone morphogenetic protein 7 gene and growth traits in chickens. Issue 3 (4th May 2018) - Wang, Y.; Guo, F.; Qu, H.; Luo, C.; Wang, J.; Shu, D.
ABSTRACT: 1. Enhancing bone strength to solve leg disorders in poultry has become an important goal in broiler production. Bone morphogenetic protein 7 ( BMP7 ), a member of the BMP family, represents an attractive therapeutic target for bone regeneration in humans and plays critical roles in skeletal development. 2. The objective of this study was to investigate the relationship between BMP7 gene expression, single-nucleotide polymorphisms (SNPs) and growth traits in chickens. Here, a SNP (c.1995T>C) in the chicken ( Gallus gallus ) BMP7 gene was identified, that was associated with growth and carcass traits. 3. Genotyping revealed that the T allele occurred more frequently in breeds with high growth rates, whereas the C allele was predominant in those with low growth rates. The expression level of BMP7 in the thigh bone of birds with the TT genotype was significantly higher than in those with the CC genotype at 21, 42 and 91 d of age. 4. These findings suggest that selecting the birds with the TT genotype of SNP c.1995T>C could improve bone growth, could reduce leg disorders in fast-growing birds. The SNP c.1995T>C may serve as a selective marker for improving bone growth and increasing the consistency of body weights in poultry breeding.